2006
DOI: 10.1097/00042737-200604000-00010
|View full text |Cite
|
Sign up to set email alerts
|

Soluble triggering receptor expressed on myeloid cells (sTREM-1): a new mediator involved in the pathogenesis of peptic ulcer disease

Abstract: sTREM-1 might be an independent factor involving with the peptic ulcerative inflammatory process that is positively correlated with histopathological abnormalities of gastritis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
24
0
1

Year Published

2007
2007
2011
2011

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 14 publications
1
24
0
1
Order By: Relevance
“…[10][11][12] Among the critically ill patients analyzed in these studies, the determination of sTREM-1 proved to be a useful and highly sensitive parameter for accurate diagnosis. Further studies where sTREM-1 is detected in patients with chronic obstructive pulmonary disease, 13 peptic ulcer disease, 14 or inflammatory bowel disease 15 confirm the involvement of TREM-1 also in noncritically ill patient collectives and suggest that the activation of TREM-1 plays a general role in the innate inflammatory response. 7 However, a deeper understanding of how TREM-1 influences inflammatory responses and sepsis requires the characterization of the natural ligand for TREM-1 and its expression pattern.…”
Section: Introductionmentioning
confidence: 75%
“…[10][11][12] Among the critically ill patients analyzed in these studies, the determination of sTREM-1 proved to be a useful and highly sensitive parameter for accurate diagnosis. Further studies where sTREM-1 is detected in patients with chronic obstructive pulmonary disease, 13 peptic ulcer disease, 14 or inflammatory bowel disease 15 confirm the involvement of TREM-1 also in noncritically ill patient collectives and suggest that the activation of TREM-1 plays a general role in the innate inflammatory response. 7 However, a deeper understanding of how TREM-1 influences inflammatory responses and sepsis requires the characterization of the natural ligand for TREM-1 and its expression pattern.…”
Section: Introductionmentioning
confidence: 75%
“…TREM-1 expression is increased during both acute ( 49,50 ) and chronic infl ammation ( 51 ). Moreover, a soluble form of TREM-1 was detected in the blood sample of human patients with infl ammatory disorders, such as sepsis ( 52 ), pneumonia ( 53 ), acute pancreatitis ( 54 ), and peptic ulcer disease ( 55 ). Very recently, Kuai et al reported that TREM-1 expression is increased in the synovium of RA patients ( 56 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the presence of elevated levels of sTREM-1 in bronchoalveolar lavage fluid is a strong predictor of pneumonia [12]. sTREM-1 is also elevated in the gastric juice of patients with gastritis, showing positive correlation with the degree of gastric inflammation scores [13]. Recently, it was reported that TREM-1 expression is involved in chronic IBD based on the observation that TREM-1 is upregulated in the intestine of patients with IBD [14].…”
Section: Introductionmentioning
confidence: 99%